REKONSTRUKSI REALITAS PEKERJA PEREMPUAN SEBAGAI YAKULT LADY DI PT YAKULT INDONESIA PERSADA KECAMATAN KANDIS, RIAU - Tumorang, Kokoria Br; Erawan, I Ketut Putra; Pramana, Gede Indra (Jurnal Nawala Politika, 2022)
This study reconstructs the reality behind women's empowerment by PT Yakult Indonesia Persada Kandis District Region. This empowerment is done by employing housewives as Yakult Lady. The Yakult Lady system is to sell Yakult products while promoting a healthy lifestyle. Based on field observations, researchers found a different reality from Yakult Lady's work. There are subtle exploits that are not visible in Yakult's communication with the Yakult Lady. Yakult utilizes the psychology of current workers who do not need to be rewarded with money but with appreciation or flattery through euphemisms for the words they communicate. This form of distribution of exploitation is a new capitalism in Indonesia. Through the critical theory of Max Horkheimer and the theory of social construction of the target group, Anne Schneider and Hellen Ingram obtained research results that the Yakult Lady is empowered and exploited at the same time.